The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fphys.2018.00823
|View full text |Cite|
|
Sign up to set email alerts
|

Significant Acute Response of Brain-Derived Neurotrophic Factor Following a Session of Extreme Conditioning Program Is Correlated With Volume of Specific Exercise Training in Trained Men

Abstract: Several studies have demonstrated an acute and chronic increase of brain-derived neurotrophic factor (BDNF) in relation to different types of physical exercise. Currently, many individuals seek physical training strategies that present different types of stimulation and volume/intensity. Thus, the extreme conditioning methodology has gained great notoriety in the scientific and non-scientific environment. Knowing that BDNF values increase in an effort-dependent manner, it is necessary to study the effects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 56 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…Some studies have reported no change in serum BDNF right after either acute or chronic exercise. On the other hand, several studies have shown that circulating BDNF increases with physical exercise (Ferris et al, 2007; Yarrow et al, 2010; Pereira et al, 2018). In skeletal muscle cells, BDNF mRNA expression is increased by contraction and increased fat oxidation through activation of AMP-activated protein kinase (Matthews et al, 2009).…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 99%
“…Some studies have reported no change in serum BDNF right after either acute or chronic exercise. On the other hand, several studies have shown that circulating BDNF increases with physical exercise (Ferris et al, 2007; Yarrow et al, 2010; Pereira et al, 2018). In skeletal muscle cells, BDNF mRNA expression is increased by contraction and increased fat oxidation through activation of AMP-activated protein kinase (Matthews et al, 2009).…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 99%
“…Despite this, perhaps further alterations in the resistance exercise protocol would be useful to consider in future research. For example, past work has demonstrated a positive correlation between the total volume of completed resistance exercise and the release of key memory-related neurotrophins, such as brain-derived neurotrophic factor (Pereira et al, 2018).…”
Section: Discussion-experimentsmentioning
confidence: 99%
“…Then, they trained a single ECP session, which consisted of a combination of highintensity multi-joint exercises with a predetermined time of 9 minutes. 21 Being re-evaluated in the moments immediately and 30 minutes after the end of the session.…”
Section: Training Sessionmentioning
confidence: 99%
“…After each successful round, an extra movement was added to each exercise, except for the double-unders or single-unders exercise, making the training session more exhaustive. 21…”
Section: Training Sessionmentioning
confidence: 99%